2015
DOI: 10.1177/0269216315583436
|View full text |Cite
|
Sign up to set email alerts
|

Enabling a family caregiver-led assessment of support needs in home-based palliative care: Potential translation into practice

Abstract: Our study has successfully addressed the call for alternatives to the professional assessment paradigm using the Carer Support Needs Assessment Tool approach as a caregiver-led intervention facilitated by health professionals. Integrating the Carer Support Needs Assessment Tool in existing practice is fundamental to achieving better caregiver outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
1
35
0
2
Order By: Relevance
“…Funnenes troverdighet i denne studien er styrket ved at de er underbygget med sitater og at de sammenfaller med andre studier (Aoun et al 2015;Candy et al 2015;Claxton-Oldfield 2015;Claxton-Oldfield et al 2010;Luijkx og Schols 2009;Solbjør et al 2014). En studies troverdighet inkluderer også funnenes overførbarhet.…”
Section: Metodiske Overveielserunclassified
See 1 more Smart Citation
“…Funnenes troverdighet i denne studien er styrket ved at de er underbygget med sitater og at de sammenfaller med andre studier (Aoun et al 2015;Candy et al 2015;Claxton-Oldfield 2015;Claxton-Oldfield et al 2010;Luijkx og Schols 2009;Solbjør et al 2014). En studies troverdighet inkluderer også funnenes overførbarhet.…”
Section: Metodiske Overveielserunclassified
“…Studier viste også at det å motta støtte og avlastning, påvirket pårørendes psykiske helse positivt på lang sikt (Ferrario, Cardillo, Vicario, Balzarino og Zotti 2004;Grande, Farquhar, Barclay og Todd 2004). Det ble derfor viktig å forbygge pårørendes helse, ved å iverksette tiltak som kunne avlaste de pårørende i forhold til den belastningen det innebar å ha hjemmeboende alvorlige syke pasienter (Aoun, Toye, Deas, Howting, Ewing, Grande og Stajduhar 2015).…”
Section: Referee* Introduksjonunclassified
“…The palliative care clinician works in partnership with caregivers and seeks to ensure that their needs are also being met . By giving caregivers permission to ask for help when they need it, including respite care, the palliative care clinician facilitates optimal patient care . Honest, clear, open communications with anticipatory guidance about what to expect as the patient's condition progresses is extremely important.…”
Section: Role Of the Palliative Care Clinicianmentioning
confidence: 99%
“…They view their patients as whole people, not simply as a diagnosis, condition, or disease. Midwives and palliative care clinicians strive to provide patient‐centered care in which the locus of control remains firmly with the patient and work in partnership with the patient's family to provide support . They recognize the need to balance technological interventions with a humanistic approach, using technology to enhance rather than drive patient care .…”
Section: Characteristics Of Midwives and Palliative Care Cliniciansmentioning
confidence: 99%
“…The CSNAT's effectiveness and utility have been tested with FCs of patients with cancer at end of life (Aoun, Deas, et al., ; Aoun, Grande, et al., ; Aoun, Toye, et al., ) showing a decrease in carer strain. Results of a trial with FCs of older people discharged home from hospital showed that FCs in the intervention group were significantly more prepared to provide care and reported reduced carer strain and distress compared to FCs in the control group (Toye et al., ).…”
Section: Introductionmentioning
confidence: 99%